Conserved leucine-rich repeat proteins in the adhesive projectile slime of velvet worms - Zhaolong Hu; Alexander Baer; Lars Hering; Ivo de Sena Oliveira; Alexandre Poulhazan; Darren C. Browne; Xue Guo; Quentin Moana Perrin; Radoslaw M. Sobota; Shawn Hoon; Georg Mayer; Srinivasaraghavan Kannan; et al. (Proceedings of the National Academy of Sciences, 2025)
The slime of velvet worms (Onychophora) is a protein-based bioadhesive that undergoes rapid, yet reversible transition from a fluid into stiff fibers used for prey capture and defense, but the mechanism by which this phase transition functions is largely unknown. Here, integrating transcriptomic and proteomic approaches with AI-guided structure predictions, we discover a group of evolutionarily conserved leucine-rich repeat (LRR) proteins in velvet worm slime that readily adopt a receptor-like, protein-binding “horseshoe” structure. Our structural predictions suggest dimerization of LRR proteins and support their interactions with conserved β-sheet-rich domains of high-molecular-weight proteins, the primary building blocks of velvet worm slime fibers. This suggests that LRR proteins might be involved in reversible, receptor-based supramolecular interactions in these biofibers, providing potential avenues for fabricating fully recyclable (bio)polymeric materials.